The influence of word of mouth and brand image on the consumer decision process in choose clinic content: Case Study of Embun Pagi Sekayu Gynecological Clinic - Ramadhayani B, Rulli; Wahab, Zakaria; Widiyanti, Marlina; Rosa, Aslamia (International research journal of management, IT and social sciences, 2022)
This study aimed to analyze the effect of word of mouth and brand image jointly and partially on consumer decisions and the dominant two variables. Data collection at the Embun Pagi Clinic in the Sekayu area involved 100 patients who used the services of the Sekayu Embun Pagi Clinic with non-probability sampling, namely accidental sampling. Data was collected by distributing questionnaires and using multiple linear regression using SPSS software. Data analysis is a descriptive method, classical assumption test with normality test with Kolmogorov-Smirnov, multiple regression analysis methods with f test, t-test, and coefficient of determination. This study indicates that word of mouth and brand image significantly influence the consumer decision process in choosing the Embun Pagi Sekayu Gynecological Clinic. These results can be seen in the multiple regression analysis and the coefficient of determination R-value of 0.802, meaning that the relationship between word of mouth and brand image on consumer decisions is 80.2%, meaning that the relationship between variables is close. Adjusted R Square value of 0.636 means that 63.6% of purchasing decision factors can be explained by word of mouth and brand image.